Pengaruh Partisipasi Anggaran dan Penekanan Anggaran Pada Senjangan Anggaran dengan Locus Of Control Sebagai Variabel Pemoderasi - Raditya, Putu Ari; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2018)
To achieve its goals, hotel requires a good planning and control to run its implementation in accordance to the policy that has been assigned. Budget is an important element and a centerpiece in the planning and control process. The aim of the current study is to find out whether locus of control can moderate the impact of budgetary participation and budget emphasis on budgetary slack. This study was conducted on 4-star hotels in Kuta district. The sampling method used was saturation. There were 30 hotels used as the sample with 97 respondents. Questionnaire was used to collect the data. To analyze the data, MRA testing was applied.The study found that locus of control could strengthen the impact of budgetary participation and budget emphasis on budgetary slack. It can be concluded that the higher the participation given and the budget emphasis moderated by locus of control, the higher the budgetary slack. Keyword : Budgetary participation, budget emphasis, locus of control, budgetary slack